L’attitude des artisans gallo-romains à l’égard du travail manuel. Étude de l’iconographie lapidaire funéraire - Marie-Sophie Caruel (Kentron, 2016)
In this article we study the attitude of Gallo-Roman craftsmen towards manual work from the way they were depicted on their funerary monuments. Two postures stand out: that of the craftsman and of the contractor. Several criteria have to be taken into account for the study of the iconographic records: the position of the images on the monument, their scale, the number of craftsmen depicted and what they are wearing.